2021
DOI: 10.3389/fmed.2021.697906
|View full text |Cite
|
Sign up to set email alerts
|

Initial Blood pH, Lactate and Base Deficit Add No Value to Peri-Arrest Factors in Prognostication of Neurological Outcome After Out-of-Hospital Cardiac Arrest

Abstract: Background: In cardiac arrest survivors, metabolic parameters [pH value, lactate concentration, and base deficit (BD)] are routinely added to peri-arrest factors (including age, sex, bystander cardiopulmonary resuscitation, shockable first rhythm, resuscitation duration, adrenaline dose) to enhance early outcome prediction. However, the additional value of this strategy remains unclear.Methods: We used our resuscitation database to screen all patients ≥18 years who had suffered in- or out-of-hospital cardiac a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In prospective observational studies, the initial lactate level had no additional value in predicting the neurological outcome of anamnesis. [21,22] Alternatively, the FFA level at 6 hours was related to the maximal troponin I level within 3 days after ROSC. Several studies reported that a high FFA level is associated with myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In prospective observational studies, the initial lactate level had no additional value in predicting the neurological outcome of anamnesis. [21,22] Alternatively, the FFA level at 6 hours was related to the maximal troponin I level within 3 days after ROSC. Several studies reported that a high FFA level is associated with myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%